Phosphorylation of HSP27 by Protein Kinase D Is Essential for Mediating Neuroprotection against Ischemic Neuronal Injury - Stetler, R. Anne (Society for Neuroscience, 2012)
Heat shock protein 27 (HSP27) (or HSPB1) exerts cytoprotection against many cellular insults, including cerebral ischemia. We previously identified apoptosis signal-regulating kinase 1 (ASK1) as a critical downstream target of HSP27 conferring the neuroprotective effects of HSP27 against neuronal ischemia. However, the function of HSP27 is highly influenced by posttranslational modification, with differential cellular effects based on phosphorylation at specific serine residues. The role of phosphorylation in neuronal ischemic neuroprotection is currently unknown. We have created transgenic mice and viral vectors containing HSP27 mutated at three critical serine residues (Ser15, Ser78, and Ser82) to either alanine (HSP27-A, nonphosphorylatable) or aspartate (HSP27-D, phosphomimetic) residues. Under both in vitro and in vivo neuronal ischemic settings, overexpression of wild-type HSP27 (HSP27) and HSP27-D, but not HSP27-A, was neuroprotective and inhibited downstream ASK1 signaling pathways. Consistently, overexpressed HSP27 was phosphorylated by endogenous mechanisms when neurons were under ischemic stress, and single-point mutations identified Ser15 and Ser82 as critical for neuroprotection. Using a panel of inhibitors and gene knockdown approaches, we identified the upstream kinase protein kinase D (PKD) as the primary kinase targeting HSP27 directly for phosphorylation. PKD and HSP27 coimmunoprecipitated, and inhibition or knockdown of PKD abrogated the neuroprotective effects of HSP27 as well as the interaction with and inhibition of ASK1 signaling. Together, these data demonstrate that HSP27 requires PKD-mediated phosphorylation for its suppression of ASK1 cell death signaling and neuroprotection against ischemic injury.